2013
DOI: 10.1161/hypertensionaha.111.00763
|View full text |Cite
|
Sign up to set email alerts
|

Novel Description of the 24-Hour Circadian Rhythms of Brachial Versus Central Aortic Blood Pressure and the Impact of Blood Pressure Treatment in a Randomized Controlled Clinical Trial

Abstract: Abstract-Elevated brachial blood pressure (BP) is associated with increased cardiovascular risk and predicts morbidity and mortality in humans. Recently, 24-hour ambulatory BP monitoring and assessment of central aortic BP have been introduced to improve BP phenotyping. The Ambulatory Central Aortic Pressure (AmCAP) study combines these approaches and describes, for the first time, the diurnal patterns of simultaneously measured 24-hour ambulatory brachial and central pressures in a prespecified substudy embed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
35
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 29 publications
7
35
1
2
Order By: Relevance
“…These data imply sustained inhibition of the RAAS with aliskiren withdrawal, while RAAS activity was gradually restored upon telmisartan withdrawal, and is consistent with other findings using these treatment types. 7,13 Persistence in the BP lowering and aldosterone lowering effects of aliskiren over the 7-day withdrawal period is consistent with tissue localisation studies with this drug. Animal studies indicate persistent accumulation of aliskiren in the kidney.…”
Section: Discussionsupporting
confidence: 75%
“…These data imply sustained inhibition of the RAAS with aliskiren withdrawal, while RAAS activity was gradually restored upon telmisartan withdrawal, and is consistent with other findings using these treatment types. 7,13 Persistence in the BP lowering and aldosterone lowering effects of aliskiren over the 7-day withdrawal period is consistent with tissue localisation studies with this drug. Animal studies indicate persistent accumulation of aliskiren in the kidney.…”
Section: Discussionsupporting
confidence: 75%
“…The study by Williams et al 7 has further merits that deserve to be emphasized. For example, the number of patients from whom the data were collected was remarkably high, considering the technical difficulty of the study and its large multicentric nature.…”
mentioning
confidence: 95%
“…[4][5][6] Studies on central blood pressure have almost invariably made measurements only in resting conditions, resting brachial blood pressure measurements serving for comparison. The study by Williams et al 7 published in this issue of Hypertension makes an important step forward by providing, via a new tonometric-based technology, central blood pressure values throughout the 24 hours and by comparing for the first time the circadian central blood pressure profile with the simultaneously measured peripheral blood pressure. The results confirm that systolic and pulse pressures are lower centrally than at brachial artery level.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The inverse relationship between heart rate and arterial compliance has also been reported in the AMCap Study. [33] Cremer et al [32] have suggested that QKD may be employed, with mean brachial systolic BP, heart rate and height, to measure central systolic BP, as a reduction in central BP is associated with better outcome. [33] It is possible that the combination of indapamide and perindopril produces benefits from either lowering Ao-PWV or central pressure or both.…”
Section: Discussionmentioning
confidence: 99%